The achievement of mathematics learning in PISA, ENLACE and PLANEA in Mexican adolescents. A retrospective analysis - Osuna Lever, Cecilia; Díaz López, Karla María (Education Policy Analysis Archives, 2020)
This article offers a historical analysis of the achievement level of mathematics learning in Mexican ninth graders. The results of the PISA, ENLACE and PLANEA tests are analyzed, with emphasis on the mathematics evaluations, given the relevance of this topic in the development of useful skills to generate technology for the 4th Industrial Revolution. In the international context, the results of the PISA test show the important gap that exists between the students evaluated in leading countries (especially the Asian ones), and the Mexican students. There is an undeniable and alarming failure in the national education system in terms of mathematics learning achievement in ninth grade students, since the results have remained low for more than 10 years in both PISA and national tests (ENLACE and PLANEA) that are aligned to the curriculum. These results reflect the great shortcomings that our students will have in the future, and the limited knowledge with which we are equipping them to work with in a globalized context where they must compete with the citizens of great world countries, whose governments, by the way, dedicate a high portion of their Gross Domestic Product to their education budgets. This will result in a disadvantageous insertion of Mexican students into the world of work and into spaces for social participation, as well as limited opportunities to continue with their formal education. The mathematics learning achievement is a great pending issue in the Mexican education policy agenda.